(untitled) (Cadernos de Sociomuseologia, 2014)
The present research focused on the ’case study’ of a local root museum process: Museu – Biblioteca Condes de Castro Guimarães, the sole institution museum in Cascais for half a century. Drawing on the epistemological field of research on Socio-museology, on primary sources, secondary and complementary bibliography, we tried to comprehend how the main founders of this institution thought, perceived and established the museological function at its origins. The research was developed in two complementary orientations: as a first step we studied the thoughts and actions of the museum curators João Couto and Branquinho da Fonseca through the content analysis methodology of their scholarly previously published texts. In parallel, we studied the history of the museum, in a diachronic perspective, starting from the 1930s until the 1980s. This allowed us to perceive that, from very early on, the social and educational functions were present and continued to be developed over the decades that followed. Those were personalities who contributed to the construction of a cultural institution, engaging in social, cultural, and educational pioneering practices to benefit the community and that we believe influenced the work of two institutions of higher magnitude and scope: Museu Nacional de Arte Antiga and Fundação Calouste Gulbenkian. Keywords - Museology, Socio-museology, Education, Local Museums, Community